Evaluasi Kualitas Air dan Tantangan Ekologi dalam Budidaya Ikan Lele di Pokdakan Margo Mulyo Abadi, Desa Berahan Kulon, Wedung, Demak - Cahyo Wulandari; Arum Nur Widya; Gesti Nola Salsabila (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
TheKKN-PPM UGM team of Wedung plays a role in supporting development in the aquaculture sector, particularly in catfish cultivation. Catfish, with their fast growth, relatively easy aquaculture techniques, and high market demand, havebecome an important fishery commodity. Pond systems are a method of catfish farming that is still widely used by the public because it is considered efficient in terms of land and water use. However, this system also faces ecological challenges, especially related to water quality, which is crucial for fish growth, health, and survival. Through this community service activity, the team conducted a study of aquatic ecology and monitored water quality in catfish cultivation pond managed by the Margo Mulyo Abadi Fish Farming Group (Pokdakan) in Berahan Kulon, Wedung, Demak. This activity was carried out to determine the current conditions and problems that occur as a reference for the implementation of further community service programs in the development of catfish aquaculture in this village. The implementation of the activity included regular weekly water quality monitoring in four selected ponds for a month, in July 2025. The data obtained were analyzed using the Indonesian National Standard (SNI) reference and related literature to assess the suitability of the parameters with the needs of catfish cultivation. The measurement results showed that the pond depth was 100 cm with salinity is 0 ppt, pH 7, and alkalinity of 180 mg/L. These results are still within the optimal range for catfish cultivation. However, there were several parameters that were less suitable, such as water temperature reaching 28–33°C, low clarity (12–16 cm), 0 m/s current speed and quite high nitrite levels reaching 1 mg/L. These conditions can impact stress, growth disorders, and fish mortality. Through these results, the team conveyed to farmers and provided recommendations regarding the importance of sustainable water quality management. Regular monitoring and good water quality management can increase sustainable productivity and maintain the sustainability of the aquatic environment.